Insights into the mechanism of antiproliferative effects of primaquine-cinnamic acid conjugates on MCF-7 cells - Mabeta Peace; Pavić Kristina; Zorc Branka (Acta Pharmaceutica)
In our previous paper, we showed that three primaquine-cinnamic acid conjugates composed of primaquine (PQ) residue and cinnamic acid derivatives (CADs) bound directly by an amide linkage (1) or through an acylsemicarbazide spacer (2 and 3) had significant growth inhibitory effects on some cancer cell lines. Compound 1 induced significant growth inhibition in the colorectal adenocarcinoma (SW620), human breast adenocarcinoma (MCF-7) and cervical carcinoma (HeLa) cell lines, while compounds 2 and 3 selectively inhibited the growth of MCF-7 cells. To better understand the underlying mechanisms of action of these PQ-CADs, morphological studies of the effects of test compounds on MCF-7 cells were undertaken using haematoxylin and eosin stain. Further analysis to determine the effects of test compounds on caspase activity and on the levels of apoptosis proteins were undertaken using the enzyme-linked immunosorbent assay (ELISA). Haematoxylin and eosin staining revealed that compounds 1 and 3 induced morphological changes in MCF-7 cells characteristic of apoptosis, while 2-treated cells were in interphase. Cell cycle analysis showed that cells treated with 1 and 3 were in sub-G1, while cells treated with 2 were mainly in interphase (G1 phase). Further, the study showed that the treatment of MCF-7 cells with 1 and 3 resulted in poly ADP ribose polymerase (PARP) cleavage as well as caspase-9 activation, indicating that they induced apoptotic cell death. We further investigated their effects on two important processes during metastasis, namely, migration and invasion. Compounds 1 and 3 inhibited the migration and invasion of MCF-7 cells, while compound 2 had a marginal effect.